"Self - regulation", "self - management", "self - organization": the correlation and psychological substance of the concepts - Kateryna Lysenko-Helembiuk (Vasyl Stefanyk Precarpathian National University, 2017)
In the article the correlation and psychological substance of the such concepts as self - regulation, self - management, self - organization and self - determine is analysed. There  are shown their special features and differences. Key words: self - regulation, self - management, self - organization and self - determine.